A Comparison Study of Fiscal Policy in Different Countries Regarding Plastic Waste Management in Supporting the Achievement of Sustainable Plastic Production and Consumption Patterns in Indonesia - Andang Wirawan Setiabudi; Gunadi; Haula Rosdiana (GoAcademica Research & Publishing, 2022)
Nowadays, plastic waste management has become an international issue. Plastic waste that is not managed will end up in the ocean and cause dangerous pollution. Environmental issues were agreed to be one of the SDGs goals proclaimed in 2015 by all countries members of the United Nations. All countries, including Indonesia, have implemented various pro-environment policies. One of them is through fiscal policy. How to determine the right fiscal policy so that the management of plastic waste to realize a sustainable pattern of plastic production and consumption to be optimal is important. One of them is by conducting comparative studies on the fiscal policy of plastic waste management in various countries as a policy benchmark. It is what the author did. This research uses a qualitative approach with a comparative study method regarding the form of fiscal policy in various countries used to manage plastic waste. This research data was obtained through literature studies from various journals, articles, and reports on fiscal policy of plastic waste management in various countries and then concluded various similarities and differences. It is hoped that studying various forms of fiscal policy in various countries can provide input to the Indonesian government on the right form of fiscal policy to create a sustainable pattern of plastic production and consumption in accordance with the SDGs goals to be achieved by the Indonesian government.